Assessment of Major and Trace Elements in Drinking Groundwater in Bisha Area, Saudi Arabia - Faleh Z. Alqahtani; Saifedin Y. DaifAllah; Yasir F. Alaryan; Abubakr M. Elkhaleefa; Eid I. Brima (Journal of Chemistry)
Drinking groundwater represents 30% of the world’s fresh water and 0.9% of the whole world’s water. Therefore, routine analysis and monitoring of the groundwater is a paramount issue, specifically the measurement of elemental concentrations due to aquifer characterization. Consequently, the purpose of this study was to determine major and trace elements in groundwater. In total, 25 samples of groundwater were collected from wells in the Bisha area, Asir province, Saudi Arabia. All samples were analyzed for major and trace elements by using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). In total, 15 elements were measured including four major elements (Na, K, Mg, and Ca) and 11 trace elements (V, Cr, Mn, Co, Ni, Cu, Zn, As, Se, Cd, and Pb). Major elements (Na, Mg, and Ca) exceeded the guideline limits in some samples. In addition, only one trace element (Se) exceeded the World Health Organization (WHO) permissible limits in some samples. This could be due to rock characteristics in aquifers. Very hard water was shown in 92% of the samples. Moreover, a high percentage (32%) of the analyzed samples also exceeded the guideline levels for chloride. ANOVA analysis showed significant difference (p<0.05) between Bisha samples (North and South), Bisha samples (North), and the remaining samples, for V and pH, and Na, Cl−, EC, and TDS, respectively. No significant differences (p>0.05) were reported for Na, K, Mg, Ca, Cr, Mn, Co, Ni, Cu, Zn, As, Se, Cd, and Pb between all samples. In general, 25 significant (p>0.05) correlations were reported among the measured elements. For the positive correlations, similar distribution for the elements is anticipated. In conclusion, the groundwater in this study is not suitable for domestic use due to its hardness and only some are suitable for irrigation. More studies are needed to confirm our findings in the study area.